Teores de carbamato de etila em aguardentes de cana e mandioca: parte II Contents of ethyl carbamate in sugar cane and manioc spirits: part II - Luiz Gualberto de Andrade Sobrinho; Luciana Tereza Dias Cappelini; Alexandre Ataíde da Silva; Carlos Alexandre Galinaro; Silmara França Buchviser; Daniel Rodrigues Cardoso; Douglas Wagner Franco (Química Nova, 2009)
Herein, we report the concentration of ethyl carbamate (EC) and copper in 380 samples of sugar-cane spirit and 45 samples of manioc spirit as determined by GC-MS and FAAS respectively. The cyanide content determined spectrophotometrically is reported for the manioc spirit. Sugar cane spirit produced by alembic distillation (70,0 µg L-1) shown a lower content of EC than samples produced by column distillation (270 µg L-1). No simple correlation between the content of EC and copper for sugar cane spirit as well among the concentration of EC, copper, and cyanide for manioc spirit could be observed.